British Association for the Advancement of Science 150th annual meeting, Oxford 5-9 September 1988: papers for section k agriculture and forestry - Savill, P (Oxford Forestry Institute, University of Oxford, 1988)
The British Association for the Advancement of Science was founded in 1831, with the object of strengthening the relationship between science and the public. From the start, an Annual Meeting has been central: the first Meeting, attended by 353 people, took place in York that same year, and except during the two world wars, meetings have been held annually ever since. Early meetings provided opportunities for major discoveries to be announced, and for scientists to share recent results. More recently, with the growing number of specialist societies and conferences, the emphasis has shifted towards the popularisation of science, and the discussion of its social consequences. Today, the meeting provides a unique forum where scientists and non-scientists can meet and discuss science and technology, and the sensitive social issues which arise from their progress evolution, molecular electronics, and science education policy are three examples from this year's programme. The meeting is Britain's only festival of science, with a rich and varied range of events, from substantial discussions on serious issues, through lectures and demonstrations to scientific visits, exhibitions, films and social events. Between 2,000 and 4,000 people come each year, many of them schoolchildren and students as well as scientists, teachers, industrialists, and public servants: people with little in common save an interest in science and its progress.